COVID-19: An Assessment of Creative Communication, Crisis Preparedness, and Resilience Building in Hospitality Business in Bali - Syafiq Basri Assegaff; Rudi Sukandar; Mike Hardy; Julia Ratnasari Dewi; Habib Mohammad Ali; Ni Putu Ayuniantari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Two years of COVID-19 pandemic have brought global consequences, especially to those operating in business. This paper examines how risk and crisis preparedness contributed to business survival and resilience in the hospitality sector in Bali, Indonesia, a market significantly dependent on international visitors. This qualitative research employing a phenomenological approach. Initial data were acquired from two months of Â observation in Bali from March 2020 until the end of May 2020. In addition to observation, semi structured interviews were also conducted with informants from four different hotels, aiming to uncover if the hotels embraced some strategies from the proactive pre-crisis planning to strategic implementations during the crisis. We did not include the after-crisis stage as the pandemic is still ongoing. The researchers validated findings through triangulating interviews with Balinese authorities. We found that although the current crisis disrupted hotel business, it also provided opportunities for creative communication, security strategies, and new connections with public sector health management. Further, in the early stages of crisis management preparedness and focused communication were vital for the level of survivability of the hotels. The study concluded that during a crisis, a successful organization management team does not follow a linear and organized process to lead their business through the stressful and chaotic phases. Based on this study, weÂ  learned that business managers who adapted to the situation with crisis preparation, combined with raised awareness of public health issues, and use of commercial strategies focused on local communities can successfully reduce threats.